Comprehensive Study of Marathi Dialects in Satara Region - Anisha Shinde Rahul Shinde (IJFL (International Journal of Forensic Linguistic), 2021)
Introduction: Marathi is an Indo-Aryan language, this language speaks many marathi peoples in the world. Dialects is an important aspect of speaker variability. Regional dialects Social dialects can help investigators to find out the speaker or author of unknown verbal as well as written communication. Aim: Comprehensive Study of Marathi Dialects in Satara Region. Objective: To extract the dialect in given samples. To express the unique quality of particular region. To identify the region of a language on the basis of regional dialect. To prepare a data base regional dialect. Methodology: The study sample include 300 recording. sample are taken in Satara district using two ways audio recording and call recording . Sample will be extracted and analysed. Region wise this is called as Regional dialect or regional words. It will be compare with standard words and unique words are differentiate in particular region. The database consists of regional dialects in Satara district. Collection of sample is done in Tehsils of Satara district. The dialect for each subject collected two times i.e. Hay, Nhay, Ratbhar, Aan, Kuth etc. Result: The study explains differences between dialects of Marathi Language, shows uniqueness of particular regional dialects. This paper existing the regional varieties of Marathi language. The attempts to addresses need to examine the Synchronic variation in selected Marathi dialects. Tue study found that the significant difference in regional language. It will be depend on type of areas, lack of education, community, caste, age, geographical status these factors affects on the language.